The Movie Novel - Gikow, Louise (New York Scholastic, 2006)
Led by a mischievous raccoon and a timid turtle, a group of woodland animals must coexist in a strange new world called suburbia. Based on DreamWorks' animated adaptation of the popular comic strip, opening in theaters on May 19. Includes a full-color 8-page insert.
Keywords: Animals -- Juvenile fiction -- Forest animals